The Effect of Brand Awareness and Brand Loyalty on Riamiranda Product Purchase Decisions (Case Study on Consumers in Palopo City) - Hasnawati Hasnawati; M. Risal; Muammar Khaddapi (Institute of Computer Science (IOCS), 2022)
This research is actually to test how much the level of significance of brand awareness and brand loyalty affects consumer decisions to buy products at the Riamiranda boutique in Palopo city. This study directly determines the sample using the saturated sample method by determining the number of samples as many as 87 samples. This study uses a quantitative research approach. The data used is primary data by distributing questionnaires to respondents. The results showed that brand awareness significantly influenced the decision to buy products at the Riamiranda boutique, Palopo city. Meanwhile, brand loyalty also significantly influences the decision to buy products at the Riamirand boutique in Palopo city. Thus it can be said that the more aware a consumer is of a quality brand and the more loyal the consumer to the brand will be a strong motivating factor for the consumer to buy the product.